Pedagogical Practices and Learning Management in Full-Day School Implementation: A Systematic Literature Review - Etikasari, Chryase; Lestari, Slamet (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
Full-Day School (FDS) has become an instructional approach adopted by many Indonesian elementary schools to extend learning opportunities while strengthening character education and improving learning management. Although numerous studies have examined FDS implementation, existing evidence remains fragmented, with limited synthesis of its pedagogical practices and learning management dimensions. This study aims to synthesize empirical evidence on pedagogical practices and learning management in the implementation of Full-Day School in Indonesian elementary education. A Systematic Literature Review (SLR) was conducted by analyzing 16 empirical studies selected through predefined inclusion and exclusion criteria following the PRISMA framework. The findings indicate that FDS provides broader opportunities for implementing character-based pedagogy, active learning, and structured instructional activities throughout the school day. Effective learning management, including instructional planning, classroom organization, and coordination between curricular and co-curricular activities, plays a critical role in achieving successful implementation. However, the review also identifies several challenges, including increased teacher workload, student fatigue, limited infrastructure, and varying levels of parental support, which influence the effectiveness of pedagogical practices. The review highlights that successful FDS implementation depends on adaptive learning management, supportive school leadership, and contextual pedagogical strategies rather than merely extending instructional time. These findings contribute to a deeper understanding of FDS as a pedagogical learning environment and provide practical implications for improving instructional quality in Indonesian elementary education.